1956
DOI: 10.1103/physrev.102.1399
|View full text |Cite
|
Sign up to set email alerts
|

High-Altitude Cosmic-Ray Neutron Intensity Variations

Abstract: For references up to 1949 **« W. P. Shaker, Phys. Rev. 80, 52 (1950)W. 0. Dmvis, Phys. Rev. 80, 150 (1950)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

1956
1956
2000
2000

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(11 citation statements)
references
References 25 publications
1
10
0
Order By: Relevance
“…These primary rays subsequently spall off their energy to other subatomic and atomic particles. The •4CO production rate has been calculated by Lingenfelter (1963) and has been compared with limited thermal neutron data (Soberman, 1956). The actual production rate is known to within 20%, but the spatial distribution of the relative production is probably better than that, because the dependence of cosmic ray flux on density and geomagnetic field strength is known better than the absolute flux of low energy neutrons at the top of the atmosphere.…”
Section: Sources Of Atmospheric 14comentioning
confidence: 99%
“…These primary rays subsequently spall off their energy to other subatomic and atomic particles. The •4CO production rate has been calculated by Lingenfelter (1963) and has been compared with limited thermal neutron data (Soberman, 1956). The actual production rate is known to within 20%, but the spatial distribution of the relative production is probably better than that, because the dependence of cosmic ray flux on density and geomagnetic field strength is known better than the absolute flux of low energy neutrons at the top of the atmosphere.…”
Section: Sources Of Atmospheric 14comentioning
confidence: 99%
“…Another approximation of Lal is that the values of absorption mean free path lengths for nuclear disintegrations derived at relatively high altitudes, 3.5^30 km [3^5], can be extrapolated to sea level. Such an extrapolation is, however, not strictly valid ( [4], p. 1408, 2nd paragraph) and will inevitably lead to a too high value for the absorption free pathlength ( [3], Table III and Fig. 4).…”
Section: Introductionmentioning
confidence: 99%
“…6 In the present report it is shown that, if a suitably extended core is assumed with its radius smaller than the nucleon Compton wavelength, then the Hofstadter new form factors, thus modified, can reasonably explain the observed mass difference.…”
Section: Acknowledgmentsmentioning
confidence: 88%
“…M ANY experiments with different methods of detection have been carried out by several authors, [1][2][3][4][5][6] in order to establish a relationship between the nucleonic intensity and the production of stars in the atmosphere, and thereby to draw conclusions about the primary cosmic radiation. In the equilibrium region of the atmosphere (200-600 gem -2 ) the intensity varied approximately according to the exponential law I=Ioe~x lL , where x is the atmospheric thickness, and L the absorption mean free path of star-producing radiation.…”
Section: Introductionmentioning
confidence: 99%